2017
DOI: 10.1007/s10151-017-1733-6
|View full text |Cite
|
Sign up to set email alerts
|

Diverticular colovesical fistula: What should we really be doing?

Abstract: Intraoperative methylene blue bladder instillation should be utilized to limit unnecessary bladder repairs. In the setting of negative methylene blue extravasation, surgeons may confidently remove urinary catheters in 7 days or less, in some cases as early as 48 h. In complex bladder repairs, cystogram is still an important adjunct, with those patients with negative studies benefiting from catheter removal at 7 days or less.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 15 publications
1
29
0
3
Order By: Relevance
“…The median duration of catheterization in the present study was 10.5 (IQR: 7.3-14.0) days. This is longer than in previous studies, in which it was reported that it is safe to remove the catheter after 7-10 days in patients with uncomplicated enterovesical fistulas [3][4][5][6]. We observed no clinical recurrences in the early postoperative period in the patients who had a cystogram.…”
Section: Discussionmentioning
confidence: 47%
“…The median duration of catheterization in the present study was 10.5 (IQR: 7.3-14.0) days. This is longer than in previous studies, in which it was reported that it is safe to remove the catheter after 7-10 days in patients with uncomplicated enterovesical fistulas [3][4][5][6]. We observed no clinical recurrences in the early postoperative period in the patients who had a cystogram.…”
Section: Discussionmentioning
confidence: 47%
“…However, the proper intra-operative management of the bladder defect and the duration of urethral catheter decompression are unclear. Other studies have questioned the need for formal bladder repair and specific intraoperative bladder management as potentially increasing operative time without significant clinical benefit in most cases [5,6,9]. Indeed, CVF was historically treated by resecting the entire fistula-including a partial cystectomy-with subsequent primary repair of the bladder defect.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CVF was historically treated by resecting the entire fistula-including a partial cystectomy-with subsequent primary repair of the bladder defect. However, several studies support the practice that in benign disease bladder resection and repair is not necessary, and that the bladder can be managed simply with Foley catheter decompression without an increased risk for bladder-related complications or fistula recurrence [5,6,9,12,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations